Effectiveness of Anger Management Training on Aggression and Social Adjustment of Working Children in Sari City - Amirnezhad, Elnaz; Heydari, Shaban; Eshaghi Gorji, Hassan (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study aimed to investigate the effectiveness of anger management training on reducing aggression and improving social adjustment among working children in Sari City.Methods and Materials: This applied study employed a quasi-experimental design with a pretest–posttest structure and a control group. The statistical population consisted of working children supported by the Behesht-e Koodakan Institute under the supervision of the Sari Welfare Organization. Thirty children aged 12–15 years were selected using convenience sampling based on inclusion and exclusion criteria and were randomly assigned to an experimental group (n = 15) and a control group (n = 15). The experimental group participated in a cognitive–behavioral anger management training program conducted in 12 weekly sessions lasting 90 minutes each, while the control group received no intervention. Data were collected using the Buss–Perry Aggression Questionnaire and the California Social Adjustment Questionnaire. Statistical analysis was conducted using multivariate analysis of covariance (MANCOVA) and univariate ANCOVA in SPSS version 27 after verifying statistical assumptions.Findings: Results of multivariate analysis of covariance indicated a statistically significant effect of anger management training on the combined dependent variables. Univariate analyses demonstrated significant differences between the experimental and control groups in aggression and social adjustment at posttest after controlling for pretest scores (p < .05). The intervention produced a substantial reduction in aggression levels and a significant increase in social adjustment scores in the experimental group compared with the control group. Effect size indices indicated that a considerable proportion of variance in aggression and social adjustment outcomes was attributable to participation in the anger management training program.Conclusion: The findings suggest that cognitive–behavioral anger management training is an effective psychological intervention for reducing aggressive behaviors and enhancing social adjustment among working children.